1993
DOI: 10.1104/pp.102.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Oxygen Defense Enzymes in Soybean (Glycine max [L.] Merr.) Root Nodules

Abstract: Soybean (Glycine max [L.] Merr.) root nodules contain the enzymes of the ascorbate-glutathione pathway to minimize oxidative damage. In the present study, fractionation and immunocytochemistry were used to determine the subcellular location of the enzymes of this pathway. AI1 four enzymes (ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase, and glutathione reductase) were present in the soluble fraction from nodule plant cells and in isolated mitochondria. No activity was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
6

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 29 publications
5
84
1
6
Order By: Relevance
“…In plants, MDHAR activity has been detected in the chloroplast, mitochondria, peroxisome, cytosol, and associated with the plasma membrane and cell wall (Dalton et al 1993;Leonardis et al 1995;Bérczi and Møller 1998;Mittova et al 2000). In this study, changes in MDHAR activity were varies depending on the development stage and the intensity and duration of water stress, with a marked increase in fruits at the mature green stage of plants stressed for 6 and 10 days (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In plants, MDHAR activity has been detected in the chloroplast, mitochondria, peroxisome, cytosol, and associated with the plasma membrane and cell wall (Dalton et al 1993;Leonardis et al 1995;Bérczi and Møller 1998;Mittova et al 2000). In this study, changes in MDHAR activity were varies depending on the development stage and the intensity and duration of water stress, with a marked increase in fruits at the mature green stage of plants stressed for 6 and 10 days (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Separated proteins were electroblotted to nitrocellulose membranes and probed with antibodies (Xiang et al 2004). Antibodies were generated to soybean root nodule ascorbate peroxidase (Dalton et al 1993) and to recombinant proteins produced in E. coli to the following ESTs: DN143131 = switchgrass CAD; DN143927 = switchgrass CCOMT; CX607415 = sorghum COMT. The coding sequence for COMT was arbitrarily truncated into N-terminal and C-terminal nonoverlapping polypeptides and used to generate polyclonal antibodies in rabbits (N-terminal) and guinea pigs (C-terminal).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Monodehydroascorbate reductase is ubiquitous in all the phylogenetic groups and its isoforms existing in chloroplasts (Hossain et al 1984), cytosol (Dalton et al 1993), peroxisomes and mitochondria (Jimenez et al 1997) have been reported. The activity of MDAR has been shown to be up-regulated under several stress conditions, for instance in tomato by salinity stress (Mittova et al 2003) and high light intensity (Gechev et al 2003), in rice by low temperature (Oidaira et al 2000), and in Arabidopsis by UV-C exposure (Kubo et al 1999).…”
Section: Introductionmentioning
confidence: 99%